Persistence of HIV drug resistance among South African children given nevirapine to prevent mother-to-child-transmission - Kanthula, Ruth (AIDS, 2017)
OBJECTIVES: We set out to examine the prevalence and persistence of mutations conferring high-level nonnucleoside reverse transcriptase (NNRTI)-resistance in a cohort of HIV-infected children who had failed prophylaxis to prevent mother-to-child-transmission (PMTCT). DESIGN: A prospective observational cohort study at the Pediatric HIV Clinic at Kalafong Provincial Tertiary Hospital in Pretoria, South Africa. METHODS: Children referred for initiation of antiretroviral therapy (ART) were enrolled from July 2010 through February 2013. HIV drug resistance testing was performed using the oligonucleotide ligation assay (OLA) on dried blood spots (DBS) collected at enrolment and monthly follow-up visits for 2 years. RESULTS: South African children who failed HIV-prophylaxis had a high prevalence of NNRTI-resistant HIV (46/88; 52%). Among children with NNRTI-resistance, the frequency of the predominant resistant variant in each child’s HIV-quasispecies was high (median 96%) at study entry (median age 7.5 months), and in 26 out of 27 followed a median of 13 months persisted at a high frequency (median 89%). CONCLUSION: Our finding that infants who fail HIV-prophylaxis frequently have long-lived NNRTI-resistant HIV suggests that resistance will likely persist through 36 months of age, when children qualify for NNRTI-based ART. These children may benefit from HIV drug resistance testing to guide selection of their treatment.